The “Evil Pleasure”: Abusive Supervision and Third-Party Observers’ Malicious Reactions Toward Victims - Xu, Erica; Huang, Xu; Jia, Rongwen; Xu, Jane; Liu, Wu; Graham, Les; Snape, Ed (Organization Science, 2020)
We investigated how abusive supervision influences interactions between third-party observers and abused victims and hypothesized when and why third parties react maliciously toward victims of abusive supervision. Drawing on the theory of rivalry, we predicted that third-party observers would experience an “evil pleasure” (schadenfreude) when they perceive a high level of rivalry with the victims of abusive supervision and that the experienced schadenfreude then would motivate third parties to engage in interpersonal destructive behaviors (i.e., undermining, incivility, and interpersonal deviance) toward the victims. We further proposed that such malicious reactions would be attenuated if groups have a high level of cooperative goals. Results based on one experimental study and two time-lagged field studies lend support to our propositions.